Patterns of smoking in Russia. Issue 1 (1st March 1998) - McKee, Martin; Bobak, Martin; Rose, Richard; Shkolnikov, Vladimir; Chenet, Laurent; Leon, David
Abstract : BACKGROUND: Tobacco is a leading cause of avoidable death in Russia but there is, as yet, relatively little information in the public domain on who is smoking and how this is changing. This information is important for those seeking to develop effective policies to tackle this issue. OBJECTIVE: To determine the prevalence of smoking in Russia and its association with sociodemographic factors. DESIGN: Cross-sectional survey on patterns of tobacco consumption. SETTING: Data were collected using the New Russia Barometer, a multi-stage stratified-sample survey of the population of the Russian Federation undertaken in the summer of 1996. PARTICIPANTS: Data were available on 1587 individuals (response rate 65.7%). Respondents differed little from the overall Russian population in terms of age, sex, education, and voting intention. MAIN OUTCOME MEASURES: Prevalence of current and past smoking. RESULTS: Smoking is common among males of all ages and in all areas. Of those aged 18–24 years, 65% smoke, rising to 73% in those aged 25–34 and then falling steadily to reach 41% in those aged 65 and older. Among women, smoking is much more common among the young (27% in those aged 18–34) than among the middle-aged and elderly (5% in those aged 55 and older), and more common among those living in urban areas than in rural areas. Smoking is also more common among men and women suffering material deprivation but there is no independent association with education. Among men, but not women, church attendance is inversely associated with smoking. In both sexes, but especially women, heavy drinking and smoking are associated. CONCLUSIONS: Tobacco poses a major threat to the health of future generations in Russia, especially among women. A robust policy response is required.